1988
DOI: 10.1038/hdy.1988.9
|View full text |Cite
|
Sign up to set email alerts
|

The genetic variation and covariation among fitness components in Drosophila melanogaster females and males

Abstract: The results presented in this study indicate low to moderate level of heritable variation for the following fitness components in Drosophila melanogaster sampled from natural population: early and late fecundity of females, virility of males and longevity of females and males. The most striking exception from this are high additive genetic variances for preadult developmental duration in both sexes. Females exhibit significant negative genetic correlations between early and late components of fitness. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
3
18
1
Order By: Relevance
“…V A and V D significantly increase with age for mortality in male fruit flies ( Hughes & Charlesworth, 1994). Similar increases were found in V A for mortality and female fecundity in the first weeks of life ( Tucic et al ., 1988 ; Engstrom et al ., 1989 ; Promislow et al ., 1996 ; Tatar et al ., 1996 ). In addition, inbreeding depression increased with age for male mortality and mating success in D. melanogaster ( Charlesworth & Hughes, 1996) but not for fecundity in Callosobruchus chinensis ( Tanaka, 1993).…”
Section: Testing the Alternativessupporting
confidence: 82%
“…V A and V D significantly increase with age for mortality in male fruit flies ( Hughes & Charlesworth, 1994). Similar increases were found in V A for mortality and female fecundity in the first weeks of life ( Tucic et al ., 1988 ; Engstrom et al ., 1989 ; Promislow et al ., 1996 ; Tatar et al ., 1996 ). In addition, inbreeding depression increased with age for male mortality and mating success in D. melanogaster ( Charlesworth & Hughes, 1996) but not for fecundity in Callosobruchus chinensis ( Tanaka, 1993).…”
Section: Testing the Alternativessupporting
confidence: 82%
“…These authors argue that changes in host use are due to changes in overall threshold for acceptage of any host, and that changes in rank order preference are not expected. Contrary to our results, 2 studies (Harrison, 1987;Prokopy et al, 1988) Although some theoretical analyses predict that genetic correlation between preference and performance could be responsible for the maintenance of genetic variation in habitat selection (Bush, 1974; but see review in Jaenike and Holt, 1991), it is well known that genetic variation in preference may exist without correlated variation in performance and vice versa (eg, Gould, 1979;Wasserman and Futuyma, 1981;Tabashnik, 1983;Futuyma and Moreno, 1988 (Courtney et al, 1989 (Tuci6 et al, 1990) and Drosophila populations (Roff and Mousseau, 1987;Tuci6 et al 1988) and which appears to contradict Fisher's (1930) (Wasserman and Futuyma, 1981) showed that a population that had been selected for female oviposition preference on a given host species displayed the same preference for this host after the selection as a population that had been maintained without choice on the same host. These findings are in agreement with our observation for the no-choice and choice Cicer lines (table I).…”
Section: Methodscontrasting
confidence: 54%
“…Where genetic correlations have been calculated from pedigreed populations of Drosophila melanogaster, some estimates between early and late fecundity have been found to be negative (Rose and Charlesworth, 1981a;Tucic et al, 1988) while others have reported positive correlations (Giesel, 1986;Engstr6m et al, 1989 The mutation accumulation theory of ageing (Medawar, 1952) (1989).…”
mentioning
confidence: 99%